Factors Hindering the Settlement of Inherited Land Disputes Due to Forgery of a Will Through the District Court - Miftahuljannah Sidik; Nur Mohamad Kasim; Sri Nanang Meiske Kamba (Universitas Negeri Gorontalo, 2023)
This research aims to identify the inhibiting factors in the settlement of inheritance land disputes caused by forgery of wills through the district court. The research uses an empirical method by analyzing interview data and a copy of case number 44/Pdt.G/2011/PN.Gtlo. The inhibiting factors are grouped into two, namely internal factors originating from the disputing parties, and external factors originating from outside the disputing parties, especially from the court. Internal inhibiting factors included the lack of witnesses, lack of good faith, lack of understanding from the parties, chaos in the trial, and lack of evidence. While external inhibiting factors include a lack of legal certainty and a shortage of Human Resources (HR) in handling land dispute cases. The results showed that legal uncertainty and lack of human resources on the part of the court had a significant impact on the process of resolving inheritance land disputes. Therefore, it is suggested that there should be improvements in the judicial system, an increase in the number and quality of human resources in the courts, as well as efforts to increase legal certainty in the handling of inheritance land dispute cases involving forged wills.